Effect of modified tapioca starch on mechanical, thermal, and morphological properties of PBS blends for food packaging - Shafi, Ayu Rafiqah; Abdan, Khalina; Ahmad Saffian, Harmaen; Mohd Dahlan, Khairul Zaman; Jawaid, Mohammad; Lee, Ching Hao (MDPI, 2018)
In this study, polybutylene succinate (PBS) was blended with five types of modified tapioca starch to investigate the effect of modified tapioca starch in PBS blends for food packaging by identifying its properties. Tensile and flexural properties of blends found deteriorated for insertion of starch. This is due to poor interface, higher void contents and hydrolytic degradation of hydrophilic starch. FTIR results show all starch/PBS blends are found with footprints of starch except OH stretching vibration which is absent in B40 blends. Besides, Broad O–H absorption in all specimens show that these are hydrogen bonded molecules and no free O–H bonding was found. SEM testing shows good interfacial bonding between PBS and starch except E40 blends. Therefore, poor results of E40 blends was expected. In TGA, a slightly weight loss found between 80 to 100 °C due to free water removal. Apart from this, insertion of all types of starch reduces thermal stability of blend. However, high crystallinity of starch/PBS blend observed better thermal stability but lower char yield. Starch A and B blends are suggested to be used as food wrap and food container materials while starch D blend is suitable for grocery plastic bags according to observed results.